Dry Stone Retaining Structures : DEM modeling. - Vincens, Eric (ISTE Press : Elsevier, 2016)
Dry stone retaining structures are structures made of individual decimeter stone blocks in contact. One advantage of this construction technology lies in the weak amount of embodied energy required for their construction, and uses only local materials. This technology may be a positive answer to the challenges brought by sustainable policies in civil engineering. Many of these structures are older than one hundred years and sustain damage due to ageing; this places the owners in front of a challenging issue. Usual scientific tools cannot address the specific behavior of such structures. Due to the discrete nature of the system, a large amount of energy can be dissipated at contact level before failure of the structure. The shape, arrangement and possible breakage of blocks may play a major role in their overall behavior, specific to these structures. This book brings an overview of the DEM technique to model the behavior of discrete civil engineering structures. Physical models, modeling and site measurements are all explored, helping the civil engineer evaluate the behavior of unique structures.